Defying gravity: The determinants of China's outbound mergers and acquisitions. - Cheng, Zhongming; Lin, Shengle (Contemporary Economic Policy, 2023)
We find that the determinants of China's outbound M&As depart dramatically from the literature. First, China's M&A volume with a target country is not affected by geographic distance, currency appreciation, or stock market return. Second, Chinese acquirers pick an unconventional uphill battle by primarily targeting countries with greater cultural distance, stronger investor protection laws, and higher per capita income. We also document that China's outbound M&As have a higher than normal percentage of deals being partial acquisitions. We argue that emerging markets can differ remarkably from developed countries in the considerations and modes of outbound M&As.